Haematological changes and iron metabolism in rats after administration of Corynebacterium parvum. - Brozovic, B. (Blackwell Publishing|1, 1975)
Administration of 1-4 mg of C. parvum to rats caused a transient and mild normochromic and normocytic anaemia with reticulocytosis. There was also an immediate and marked fall of plasma iron concentration and a moderate increase of total iron binding capacity of plasma. Despite increased clearance of 59Fe from the plasma there was no significant change of the plasma iron turnover rate. At later intervals after administration of C. parvum an increased incorporation of iron into red blood cells and the spleen was observed. These changes in iron metabolism have been explained in terms of increased retention of iron in the mononuclear phagocyte system during the first few days after C. parvum and enhanced erythropoiesis at later intervals. Other haematological parameters remained normal, with the exception of the absolute number of lymphocytes, which initially fell sharply but soon returned to, and even exceeded, control levels. Liver and spleen weights increased greatly after administration of C. parvum, reaching a maximum at the end of the first week, and both these organs contained mononuclear cell infiltrates, granulomata and giant cells.